An anthropometric study of the external ear in the Thai population. Issue 4 (April 2022) - Khobkhun, Phatwira; Pungrasmi, Pornthep; Suwajo, Poonpissamai; Nilprapha, Kasama; Meevassana, Jiraroch; Promniyom, Pasu; Angspatt, Apichai; Jindarak, Sirachai; Iamphongsai, Seree
Abstract: Auricular dimensions are important data for the treatment of auricular deformities, either congenital or acquired. Many previous studies have shown that the auricular dimension varies among ethnic groups; however, there are currently no available data for the Thai population. The objective of this investigation was to provide normative values regarding the adult ear dimensions in Thailand. A total of 200 Thai volunteers between the ages of 18 and 70 years (80 men, 120 women) were enrolled in this study. We measured six dimensions, including the auricular, lobular, and conchal length and width and the auricular projection at the superaurale and tragal levels. Moreover, we calculated the auricular, lobular, and conchal indices. The selected dimensions of the external ears were shown as means ± standard deviations. These parameters were then compared between the right and left sides, men and women and participants aged ≥50 and <50 years. We found that men have a significantly larger and more projected ear than women do. The length of the entire auricles and the length of the earlobe were also significantly longer in the population ≥50 years than those <50 years. This study provides normative data of the external ear dimension and projection in the adult Thai population. These data can be used to reconstruct the ear and face more appropriately for Thai individuals.